A practical approach to special care in dentistry - Dios, Pedro Diz editor Ph. D.; Kumar, Navdeep Ph. D.
A Practical Approach to Special Care in Dentistry delivers an overview of special care dentistry reflecting the most common compromised clinical conditions dentists will regularly encounter. It discusses more than 50 topics based on real-world clinical cases focusing on two main areas: patients with disabilities and medically compromised patients. The book uses a problem-based learning approach and helps the reader to apply knowledge in a clinical case context. Each chapter contains a case report establishing the main risk factors relating to the provision of dental treatment. That is followed by a practical and realistic set of adaptations for the reader to follow to minimise the rate and severity of potential complications for their patient.